2017
DOI: 10.1136/jech-2016-208556
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic differences in children’s growth trajectories from infancy to early adulthood: evidence from four European countries

Abstract: Significant differences in children's height by maternal education persist in modern child populations in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
(24 reference statements)
1
19
1
Order By: Relevance
“…On the contrary, Clegg, Pawson, Ashton, and Flinn (), using Ethiopia children's data, found that highland children (living at ~3000 m), particularly boys, were taller, heavier, and bigger in most physical dimensions than were lowland children (living at ~1500 m). Furthermore, the effect of socioeconomic inequalities on height have been consistently observed within and between populations, with disadvantaged groups tending to be shorter in adulthood (Crespo, Valera, Gonzales, & Guerra García, ; Howe et al, ; McCrory et al, ; Silva et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Clegg, Pawson, Ashton, and Flinn (), using Ethiopia children's data, found that highland children (living at ~3000 m), particularly boys, were taller, heavier, and bigger in most physical dimensions than were lowland children (living at ~1500 m). Furthermore, the effect of socioeconomic inequalities on height have been consistently observed within and between populations, with disadvantaged groups tending to be shorter in adulthood (Crespo, Valera, Gonzales, & Guerra García, ; Howe et al, ; McCrory et al, ; Silva et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of social inequalities in growth and childhood overweight in high-income countries has been highlighted in recent years (Ballon et al, 2018;Barriuso et al, 2015;Howe et al, 2012;McCrory et al, 2017). These inequalities are observed as early as the first day of life, since positive associations have been described between socioeconomic position and both weight and length at birth (Ballon et al, 2018;Howe et al, 2012;Jansen et al, 2009;Mortensen, Helweg-Larsen, & Andersen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We show that a latent growth model provides a unified testing framework, permitting separate estimates for within-and between-group catch-up in the same specification. Latent growth models have been used to quantify and explain (socio-economic) gradients in child growth outcomes (e.g., McCrory et al 2017), but they have not been widely used to test for the presence of catch-up growth. Moreover, as we discuss, such models address a number of shortcomings associated with conventional empirical tests of catch-up growth.…”
mentioning
confidence: 99%